Theological Complicity in the Disappearing of the Working Class. Issue 1 (March 2016) - Posadas, Jeremy
Abstract: Contrary to popular perception, the majority of the United States population belongs to the working class, not the middle class (even under different definitions of class). But in the discourses of policy‐making, popular culture, and Christian theological scholarship alike, the working class has almost completely disappeared—which contributes to deifying economic and political inequalities. To counteract this disappearance, class must be established as a constructive theological locus, and justice for the working class (qua working class) established as both ethical norm and practical objective.